Up-to-date Clinical Trials of Hair Regeneration Using Conditioned Media of Adipose-Derived Stem Cells in Male and Female Pattern Hair Loss - Shin, Hyoseung; Hyun Won, Chong; Chung, Woon-Kyung; Park, Byung-Soon (Current Stem Cell Research & Therapy, 2017)
Background: The primary roles of mesenchymal stem cells (MSCs) are to maintain the stem cell niche, facilitate recovery after injury, and ensure healthy aging and the homeostasis of organ and tissues. MSCs have recently emerged as a new therapeutic option for hair loss. Objective: Since adipose-derived stem cells (ADSCs) are the most accessible sources of MSCs, ADSCbased hair regeneration is investigated. Besides replacing degenerated cells in affected organs, ADSCs exhibit their beneficial effects through the paracrine actions of various cytokines and growth factors. Results: Several laboratory experiments and animal studies have shown that ADSC-related proteins can stimulate hair growth. In addition, we introduce our clinical pilot studies using conditioned media of ADSCs for pattern hair loss in men and women. Conclusion: We believe that conditioned media of ADSCs represents a promising alternative therapeutic strategy for hair loss. We also discuss practical therapeutic challenges and the direction of future research.
Keywords: Adipose-derived stem cell